Apakah Kinerja Saham Syariah Lebih Baik Dibandingkan Saham Non-Syariah pada Tahun 2018-2019? - Eka Maya Sari; Tri Gunarsih (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2021)
There are two considerations that investors need to notice if they want to invest in the capital market, namely, return and risk. An investor needs to diversify to gain benefits and minimize risk by forming the optimal stock portfolios. This research analyzes the differences between Islamic stock (based on JII) and non-Islamic stock (based on LQ45) stock portfolio investment using the single index model. The samples were consistently listed on the JII and LQ45 stock indices in January 2018-December 2019. There are 35 stocks for the LQ45 stock index and 25 stocks on the JII stock index. Sharia stocks' optimal portfolio comprises three stocks, while the optimal portfolio of non-Islamic stocks shall consist of four stocks. The Independent Sample T-Test was implemented to analyze the differences between the Islamic (JII) and non-Islamic (LQ45) optimal stock portfolios based on the Sharpe Ratio, Jensen Ratio, and Treynor Ratio. The results show that there is no significant difference between Islamic and non-Islamic stocks.